Dimensões didática, afetiva e formativa de docência que tecem as representações sociais entre licenciandos da UFPI - Soares, Norma Patricya Lopes (2012)
This study intends to analyze the social representation of teaching for students of first years of undergraduate courses in Education, Letters and Biology. The field of this research was the Federal University of Piaui - Campus of Picos in 2009. To reach the objective proposed above, was used the theory of social representations to the seizure of the elements which constitute such representations according to Moscovici and colleagues, considering the contribution of Abric with his Theory of Central Nucleus and Wagner with the Theory of Sociogenesis. Data were collected in two phases: first, through the Technique of Free Association of Words (TFAW) of which 100 subjects evoked representations of their teaching through the inductor terms 'to teach', 'student' and 'teacher'. For those data we used the EVOC software that promoted to detect the elements of the core and to conclude that the social representation of teaching is one of the work performed by a master / teacher who transmits, directed to an apprentice who learns, confined to the school involving the student with all his virtues to be smart, interested and dedicated, and teacher to be friend, wise bearer of knowledge and also intelligent. Then, using the Multiple Classification Procedure (MCP) only 10 subjects made ratings of 25 more evoked words in the first phase, for the analysis of data from the MPC with the use of the SPSS software we used Multidimensional Statistical Analysis (MSA) for the Free Classification we found three dimensions of Social Representation of Teaching: The Didactic, that focuses on teacher and student being superimposed, meaning the inseparability of these elements, the Affective, which presents the elements inherent in teachers with love as the strong point of this dimension, and the Formative, that is as ambiguous as ambivalent because it sees the teacher as a professional directed to help students get an education; for Directed Classification with Similarity Structure Analysis (SSA), we learn that teaching is a profession that materializes in the classroom, which is extremely true because the action happens in this teaching space, supposing a caring, loving, cheerful, capable, apt, patient, partner, responsible, dedicated, committed educator, who has wisdom and knows how to teach and help students through dialogue to there study and learning. All of it s necessary to occur the result of teaching, which is education in a disciplinary manner. The results point to a very traditional social representation of what is the role of teachers, the role of students and the role of the relationship itself between teaching and learning through the act of teaching. With this statement, we can confirm that the structure of Social Representation of Teaching for the investigated subjects reflects the sociogenetic conditions that engendered them, and that these conditions permeate their structural organization, in particular time-context in which social representation was captured